The rural telecommuter surplus in Southwestern Ontario, Canada. (April 2019) - Hambly, Helen; Lee, Jamie (Donghoon)
Abstract: This paper asks the question: what kind of economic benefits do rural telecommuters experience in Southwestern Ontario? This is a relevant question in Canada where, according to Statistics Canada (2017) one in 14 people work from home. This paper presents an overview of the current literature on telecommuting. We estimate the telecommuter surplus in Southwestern Ontario where the region is currently deploying one of Canada's largest publicly-funded ultra-high-speed broadband initiatives known as SouthWest Integrated Fibre Technology Inc. (SWIFT). The analysis is based on SWIFT residential and farm surveys (n = 3948) conducted in 2017. We find that an average telecommuter's surplus in terms of costs saved, including opportunity cost ranges from $8820 to $23964 per annum per telecommuter, depending on the number of days telecommuted per week for home and primary residence dwelling type. The social net benefits of telecommuting differ from its private net benefit (the focus of our paper) since the former includes both positive and negative externalities associated with telecommuting such as reduced traffic congestion, reduced probability of road accidents, as well as some workers shirking their duties (a negative impact). We leave this for future work. Highlights: Reliable high-speed internet enables telecommuting. Telecommuting is widespread across SW Ontario. The annual surplus for three days a week is at least CAD$13, 980 for the first telecommuter. As current connectivity improves the rural telecommuter surplus will rise.